Celiac Disease by the Age of 13 Years Is Not Associated With Probiotics Administration in Infancy. Issue 6 (June 2018) - Savilahti, Emma Merike; Ilonen, Jorma; Kukkonen, Anna Kaarina; Savilahti, Erkki; Kuitunen, Mikael
Abstract : ABSTRACT: Probiotics are theoretically promising in primary prevention of celiac disease (CD), but research evidence on the topic is scarce. We used the data and material of a clinical double-blind randomized placebo-controlled trial on primary allergy prevention (n = 1223) to investigate in an exploratory study whether administration of a mix of pro- and prebiotics during late pregnancy and first 6 months of life was associated with prevalence of CD during 13-year follow-up. Children who fulfilled diagnostic criteria for CD (n = 11) and subjects with a serum sample available for analyzing CD antibodies (n = 867) were included. CD or elevated tissue transglutaminase IgA antibodies were not associated with probiotics or placebo. Nor were there any associations with the mode of delivery, the duration of exclusive or total breast-feeding, or respiratory infections during the first 2 years of life. Allergic diseases or sensitization by the age of 2 or 5 years were not clearly associated with the development of CD.